Development of Parental Efficacy Scale to Measure Parents’ Involvement Capabilities in Elementary Education: Array - Yosef Yosef; Hasmalena Hasmalena; Sigit Dwi Sucipto (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2021)
Parental involvement had benefit for the education of elementary children. Yet, knowing parental efficacy was important factor to do such involvement. The purpose of this study was to design and examine a practical, valid, and reliable parental efficacy scale for measuring parents’ capabilities to involve in elementary education. A total of 402 parents of elementary children participated in this study, consisting of 114 fathers (28.36%) and 288 mothers (71.64%). They were selected randomly from 10 elementary schools and fulfilled informed consent showing they participated voluntarily in the study. A Parental Efficacy Scale which had been designed was tested for its practicality, validity and reliability. This self-report instrument asked parents to respond 67 items containing six aspects, namely their belief to be able parenting children, communicating with the school, helping children learn at home, becoming school volunteers, making decisions, and collaborating with community. The results showed that the scale fulfilled all of three requirements in all six aspects.